Sequencing and de novo assembly of a near complete indica rice genome - Huilong Du (Nature Portfolio, 2017)
High-quality reference genomes facilitate analysis of genome structure and variation. Here Duet al. create a near-complete assembly of the indicarice genome by combining single molecule sequencing with mapping data and fosmid sequences and identify genetic variants by comparison with other rice genomes.